Особенности определения достоверности входного контроля знаний студентов - Малышкина, Е. С. (ХНУРЕ, 2009)
In the given work the reliability of entrance inspection of students’ knowledge is determined with the use of sampling methods for inspection by attributes.
Keywords: контроль знаний студентов